A favela Cabana do Pai Tomás: a ocupação consentida: memória e história - Cunha, Álisson Veloso da (2003)
Studying one ofthe biggest slums ofBelo Horizonte city, Cabana do Pai Tomás, I intended to construct it’s memory and it’s history, reminding and remembering the inhabitants’ diaiy fights for the conquer o f their space to live, starting with the downfall o f an immense Eucalyptus area planted by the businessman and Federal Congressman Antônio Luciano Pereira Filho, considered by them as the fírst invader. I aim to show, by means of the remembrances present in the inhabitants’ memory, how was the inhabited area before the occupation, the troubles faced on the building of the shanties, as for example the police’s repression, conquests like water, electrical energy, transport, education, the existent feelings, who helped them with the occupation process, the internai fights for the leadership ofthe Moviment, as like the quotidian scenes. I intended to relate the occupation movement o f the Cabana do Pai Tomás shantytown to the political, social, economic questions that was occurring into Belo Horizonte city at that moment, questions which can be considered directly responsible for the start o f the area’s occupation process. In this study I also aim to valorize and preserve the remembrances present in the memories o f memories o f the inhabitants, who contributed immensely for its arising and growing, and of the people whose help was important for the occupation process. This study has as the main research’s source the inhabitants’ depositions, giving priority to those who participated ofthe occupation and the people joined to them, besides o f bibliographical references, pictures and maps.